ANALISIS DIVERSIFIKASI CIOETANOL DI PT PERTAMINA (PERSERO) - , Wiedhi Akbar Nugroho ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. Pertamina (Persero) as a provider of petroleum products can not meet the needs of fuel consumption in the country especially in the sector of land transportation is always an increase of about 8% per year despite increasing production capacity every year both production and reserves. PT. Pertamina (Persero) still rely on the capacity of the national oil reserve as the main source of raw materials to produce products derived crude oil reserves while the total national capacity can only meet the needs of the country for 18 years. Therefore, the strategy of product diversification of fuel should be taken to reduce its dependence on oil and increase energy security. Bioethanol is one option for the development of fuel due to the renewable fuel, have high energy and friendly to the environment. The purpose of this study to analyze horizontal diversification strategy bioethanol in PT. Pertamina (Persero) using the method of the value chain. The data in this study were analyzed qualitatively, namely primary data obtained from interviews and secondary data in the form of the theory, the definition and substance of the literature and then analyzed using analysis of the value chain in order to get a conclusion about a horizontal diversification strategies and constraints faced. Based on the analysis, it is concluded that ethanol can be synergism with fossil fuels value chain because there are some similarities in both primary and support activities to maximize resource empowerment without making significant changes. However, the availability of raw materials that do not intersect with the needs in the food sector to be the main obstacle in the development of bioethanol because the ability of raw materials to produce ethanol is low so the import is an option to meet the needs in the food sector and requires the availability of vast tracts of land and the use of raw materials as well determine the need for bioethanol processing facility design. Therefore, the research and development of materials that do not intersect with the needs of the food sector with relevant parties to the implementation option long term strategy to reduce dependence on crude oil.